The Impact of the English Reading Learning Media Excluding the Braille Facility for Visually Impaired Students - Ni Putu Ratni; Geminastiti Sakkir (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2026)
This research was motivated by the learning environment's failure to provide resources that accommodate the sensory needs of students with visual impairments at UHN IGBS Denpasar; The purpose of this study describe the learning conditions and English reading practices of students with visual impairments in the absence of Braille facilities, and to analyze the academic and pedagogical impacts of this lack on the development of their reading skills; the research utilized a qualitative approach, employing qualitative descriptive methods and triangulation-based analytical approach; the findings indicated that English reading instruction without Braille support creates suboptimal learning conditions for students with visual impairments. The findings indicate that the absence of accessible textual resources limits students' opportunities to interact directly with written language, develop reading proficiency, and participate independently in learning activities. This study had a limited number of participants and focused only on English reading skills, which posed certain constraints. Therefore, it is suggested that future researchers explore this area of study using a broader range of data sources and locations.